2019
DOI: 10.1136/archdischild-2019-318258
|View full text |Cite
|
Sign up to set email alerts
|

Mobile device applications and treatment of autism spectrum disorder: a systematic review and meta-analysis of effectiveness

Abstract: ObjectiveThe current study was performed to assess the evidence for effects of therapeutic intervention with mobile device applications (apps) for individuals with autism spectrum disorder (ASD).DesignThe main methodology of the current study was systematic review with meta-analysis.SettingOnly randomised controlled trials (RCTs) for mobile device apps for individuals with ASD were considered for review in the current study.PatientsThe target population was individuals clinically diagnosed with ASD.Interventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 25 publications
(25 reference statements)
0
10
0
Order By: Relevance
“…Avatar-based therapy can be implemented at regular intervals via online meeting platforms and the sessions can be recorded to analyze the child's improvement. Moon et al (2020) performed a study to demonstrate the effects of therapeutic intervention with smart phone applications for individuals with ASD. As the results show, using smart phone applications is promising for therapeutic intervention for individuals with ASD.…”
Section: Future Research Directionsmentioning
confidence: 99%
“…Avatar-based therapy can be implemented at regular intervals via online meeting platforms and the sessions can be recorded to analyze the child's improvement. Moon et al (2020) performed a study to demonstrate the effects of therapeutic intervention with smart phone applications for individuals with ASD. As the results show, using smart phone applications is promising for therapeutic intervention for individuals with ASD.…”
Section: Future Research Directionsmentioning
confidence: 99%
“…Research has shown that autism features useful for diagnosis and continuous phenotyping can be detected in short home videos taken by smartphones [17-19, 23-24, 38, 54-55, 59, 64]. Interactive devices such as smartphones are increasingly being evaluated for use in at-home digital diagnostics and therapies which adapt to the needs of the child [43]. For diagnostics, computer vision classifers measure the behavior of the child, and statistical measurements are used to provide a diagnosis or screening [13-14, 58, 75].…”
Section: Introductionmentioning
confidence: 99%
“…Interactive devices such as smartphones are increasingly being evaluated for use in at-home digital diagnostics and therapies which adapt to the needs of the child [31]. For diagnostics, computer vision classifiers measure the behavior of the child in real-time, and statistical measurements are used to provide a diagnosis or screening [10,43,55].…”
Section: Introductionmentioning
confidence: 99%
“…Hong and colleagues reported similar positive results in their systematic review of single case studies on the effectiveness of tablet-mediated interventions for people with ASD [ 18 ]. Recently, Moon and his colleagues conducted a systematic review with meta-analysis to evaluate the effectiveness of mobile device intervention in randomized controlled trials (RCTs) [ 19 ]. The meta-analysis showed positive results, suggesting that mobile interventions could significantly improve performance in the fine motor and visual areas.…”
Section: Introductionmentioning
confidence: 99%
“…RCTs in this area have increased in recent years. Even though the review conducted by Moon and his colleagues [ 19 ] provided positive evidence concerning the effectiveness of mobile intervention in people with ASD, a more detailed investigation where the characteristics of these trials are particularly useful would be crucial, as the findings could provide useful practical implications for designing future RCTs in this area. As a result, this systematic review focuses on currently available RCT studies with the following specific research question: What are the crucial characteristics that contribute to effective mobile intervention to promote social and cognitive skills among people with ASD?…”
Section: Introductionmentioning
confidence: 99%